До питання про визнання збройного конфлікту в Афганістані після 11 вересня 2001 року збройнйм конфліктом міжнародного характеру. - Процун, С.С.; Процун, С.С.; Procun, S (My University, 2011)
The article deals with the problem of recognition of international war against global terrorism as international armed conﬂ ict in the meaning of the Geneva conventions. It argues that application of the right to self-defence as justiﬁ cation for military interventions by the US, as well as urgent need to regulate the antiterrorist operations and secure human rights make it pos- sible and necessary to grant the status of the international armed conﬂ ict to the war against terrorism by drafting an additional protocol to the Geneva conventions.
Процун, С.С. До питання про визнання збройного конфлікту в Афганістані після 11 вересня 2001 року збройнйм конфліктом міжнародного характеру. / С.С.Процун // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України, НУ ОЮА. – Одеса : Фенікс, 2011. – Вип. 43. С.109 - 119.
Keywords: Збройні конфлікти; Визнання конфлікту в Афганістані; Збройні конфлікти міжнародного характеру; Міжнародний тероризм; Международний терроризм; Вооруженные конфликты международного характера; Признание конфликта в Афганестане; Вооруженные конфликты; Armed conflicts; Recognition of the conflict in Afganestane; The armed conflicts of an international character; international terrorism